The Effect of Management's Choice between Negotiated and Competitive Equity Offerings on Shareholder Wealth - Bhagat, Sanjai (Journal of Financial and Quantitative Analysis, 1986)
Sanjai Bhagat, The Effect of Management's Choice between Negotiated and Competitive Equity Offerings on Shareholder Wealth, The Journal of Financial and Quantitative Analysis, Vol. 21, No. 2 (Jun., 1986), pp. 181-196